2006
DOI: 10.1262/jrd.17066
|View full text |Cite
|
Sign up to set email alerts
|

Basal Body Temperature Method for Detecting Ovarian Cycle in the Captive Beluga (Delphinapterus leucas)

Abstract: Abstract.The relationship between basal body temperature and circulating progesterone levels were investigated in a female beluga. Body temperature and serum concentrations of progesterone were measured daily and at 2-4 week intervals respectively, in a female beluga that was in captivity for 7 years between 1996 and 2003. The beluga first ovulated in April, 2000 (13 years old). Thereafter, serum concentrations of progesterone showed cyclic changes, indicating that the ovulatory cycle had started. Serum concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…However, changes in temperature during the estrous cycle in killer whales were not examined in the earlier study. Increasing body temperature corresponded to the luteal phase during the estrous cycle in the killer whale used in our study, which is similar to what has been reported in female belugas [Katsumata et al, 2006b] and terrestrial mammals, such as the Asian and African elephants [Kusuda et al, 2007c]. In female belugas, it has been reported that changes in body temperature are positively correlated with serum progesterone concentrations during the estrous cycle [Katsumata et al, 2006b] and, in elephants with normal estrous cycles, the body temperature is higher during the luteal stage [Kusuda et al, 2007c].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, changes in temperature during the estrous cycle in killer whales were not examined in the earlier study. Increasing body temperature corresponded to the luteal phase during the estrous cycle in the killer whale used in our study, which is similar to what has been reported in female belugas [Katsumata et al, 2006b] and terrestrial mammals, such as the Asian and African elephants [Kusuda et al, 2007c]. In female belugas, it has been reported that changes in body temperature are positively correlated with serum progesterone concentrations during the estrous cycle [Katsumata et al, 2006b] and, in elephants with normal estrous cycles, the body temperature is higher during the luteal stage [Kusuda et al, 2007c].…”
Section: Discussionsupporting
confidence: 91%
“…However, information about the relationship between body temperature and reproductive stages, such as the estrous cycle and pregnancy, is very limited in cetaceans. There are a few reports about changes in body temperature in parturition in bottlenose dolphins ( Tursiops truncates ) [Terasawa et al, 1999], in pregnancy and parturition in killer whales [Katsumata et al, 2006a], and with the estrous cycle in belugas ( Delphinapterus leucas ) [Katsumata et al, 2006b]. However, a relationship between body temperature and the circulating progesterone concentration with the estrous cycle has not been reported in killer whales.…”
Section: Introductionmentioning
confidence: 99%
“…This could potentially be a result of using data from two species with different (D/L) 0 values, but could also be caused by a lower core temperature of fin whales (36.18C, from George et al 1999) than that of narwhals. However, the core temperature of the beluga whale, the narwhal's closest relative, has been measured to 358C (Katsumata et al 2006), and we assume narwhal core temperature to be similar. But, this is only speculation as no records of narwhal core temperature are available in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the basal body temperature has been reported to be an effective method of documenting the estrous cycle [7] and to be an indicator of corpus luteum activity in cows [8]. A relationship between the ovarian cycle and body temperature has been also reported for several species of marsupials, such as the Tasmanian bettong (Bettongia gaimardi) [9], common wombats (Vombatus ursinus) [10] and marine mammals such as the beluga (Delphinapterus leucas) [11]. Furthermore, in some mammals, such as sheep [12], cattle [8], bottlenose dolphins (Tursiops truncates gilli) [13] and killer whales (Orcinus orca) [14], a decrease in body temperature has been observed from several hours to several days before parturition.…”
Section: )mentioning
confidence: 99%